Candy Cotton Machine - Ahd Odeh, Noor Hamdan (My University, 2024)
In the realm of traditional candy machines burdened by manual operation, our project comes as an innovative solution. Focused on enhancing the conventional candy-making experience, we integrate advanced technological features to automate and improve efficiency. This addresses the challenges of manual processes, offering a modernized approach to traditional candy production. Our project unveils an exceptionally candy-making experience. The project will begin with the construction of the basic ingredients of the candy cotton machine, ensuring its basic function of producing cotton candy. Furthermore, our system seamlessly automates sugar addition, dynamically altering its color. Additionally, our project introduces a controlled arm, so it automatically assembles candy cotton without the need for human impact. The project creates an interactive environment, empowering users to select a the candy cotton. the machine initiates production by guiding the flow of sugar in a specific color into the core mechanism, fashioning the candy cotton. The final touch is bestowed by the arm, meticulously shaping the candy. This means that the user chooses the shape through a mobile application, and the arm is responsible for making a candy cotton, provided that the appropriate color is chosen and produced using the heater and motors. 5